The Relationship Between Breast Care and Breast Milk Production Among Postpartum Mothers - Aisyah, Aisyah; Juliati, Juliati; Hasanah, Nur; Agustina, Dedek (Jurnal Keperawatan Priority, 2025)
The postpartum period plays a critical role in establishing successful breastfeeding. Adequate breast milk production is essential to meet the nutritional needs of infants, particularly during the first 1,000 Days of Life (HPK), a window that significantly impacts a child's growth and development. Among the various factors that influence lactation, consistent and proper breast care practices by postpartum mothers are believed to support milk production. This study employed an analytical observational design using a cross-sectional approach. A total of 32 postpartum mothers at Klinik Pratama Hugo Hasena were selected through a total sampling technique. Data on breast care practices and breast milk production were collected using structured questionnaires and analyzed using the chi-square statistical test. The findings revealed that the majority of mothers (81.3%) performed breast care routinely, and the same proportion (81.3%) reported sufficient breast milk production. Statistical analysis showed a significant relationship between breast care and breast milk production (p = 0.000). The study concludes that breast care has a significant association with breast milk production among postpartum mothers. These results highlight the importance of educating and empowering mothers on proper breast care techniques as part of postnatal support to promote successful breastfeeding. Healthcare providers are encouraged to enhance postpartum education programs, particularly focusing on the role of breast care in supporting optimal lactation and infant health during the critical early stages of life.